A potato cream dressing and process for its preparation

CN121926872BActive Publication Date: 2026-10-27THE FIRST AFFILIATED HOSPITAL OF SUN YAT SEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610399824.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-30
Publication Date
2026-10-27
Estimated Expiration
2046-03-30

AI Technical Summary

Technical Problem

该方法有效解决了马铃薯提取物中活性成分易氧化分解,药效持续性短,乳膏稳定性差,整体抗炎、抗氧化、保湿性能不理想的问题

Benefits of technology

本发明制备的乳膏敷料中,通过PLGA 包覆马铃提取物并采用PNIPAM锚定,提高了提取物在乳膏中的稳定性,抑制其在了乳膏中分层、沉降,保证乳膏的质地细腻,配合α-茄碱、α-卡茄碱形成快速起效+长效作用的协同靶向抗炎体系,有效提高了乳膏的抗炎保湿效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121926872B_ABST
    Figure CN121926872B_ABST
Patent Text Reader

Abstract

The application relates to a potato cream dressing and a preparation process thereof, and belongs to the technical field of medical dressing products. The potato cream dressing is prepared by the following steps: preparing potato extract through enzymolysis and ultrasonic-microwave combined extraction, preparing PLGA composite nanoparticles by mixing the potato extract with PLGA, then performing emulsification treatment and segmented cooling on the PLGA composite nanoparticles together with poly-N-isopropyl acrylamide (PNIPAM), alpha-solanine, alpha-solamargine, potato starch and potato protein powder to prepare the cream dressing, and adding hydroxypropyl ethyl ester in the segmented cooling process. In the prepared cream dressing, the potato extract is coated by PLGA, and is anchored by PNIPAM, so that the stability of the extract in the cream is improved, the stratification and sedimentation of the extract in the cream are inhibited, the texture of the cream is ensured to be fine, a synergistic targeted anti-inflammatory system with fast effect + long effect is formed by alpha-solanine and alpha-solamargine, and the anti-inflammatory and moisturizing effects of the cream are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical dressings, specifically to a potato cream dressing and its preparation process. Background Technology

[0002] Skin wound repair is a key focus in the medical field. Natural active ingredients, due to their good biocompatibility and low side effects, occupy an important position in wound repair dressings. Potatoes, as a globally abundant and economically important crop, contain active ingredients such as solanines, polysaccharides, and proteins, which have been proven to possess anti-inflammatory, cell proliferation-promoting, and wound-healing pharmacological activities. Topical creams developed based on potato active ingredients are gradually becoming a research hotspot. However, currently commercially available topical skin repair dressings and potato-related creams generally suffer from multiple technical bottlenecks, and their core performance cannot meet the precise treatment needs of medical wound repair, thus limiting their effectiveness in clinical applications.

[0003] Low utilization rate of active ingredients is the primary challenge. In traditional preparation processes, potato active ingredients are mostly obtained using ultrasonic extraction technology. This method can only release 30%-40% of the key active ingredients such as solanine, polysaccharides, and proteins from the raw materials, resulting in a significant waste of effective substances. At the same time, due to the lack of a targeted delivery system, the active ingredients, after being directly dispersed in the matrix, have difficulty penetrating the skin's stratum corneum barrier, resulting in low transdermal absorption efficiency. Most of the components remain only on the skin surface and cannot reach the deeper layers of the wound to exert their repair effects, leading to a mismatch between the value of the raw materials and the efficacy of the formulation.

[0004] The inadequate stability and skin compatibility of dressing formulations are also prominent issues. Most existing products use a single emulsion system, which is prone to delamination and disintegration under extreme storage or use conditions (such as freezing at temperatures below -20°C or transportation at temperatures above 50°C), leading to dressing formulation failure. Furthermore, the formulation has poor spreadability when applied to wounds and insufficient adhesion to damaged skin, failing to create a continuous drug release environment and further affecting the repair effect.

[0005] A singular repair mechanism leads to low wound healing efficiency. Most current products rely solely on basic moisturizing or simple anti-inflammatory ingredients, failing to establish a synergistic mechanism of "microecological regulation-cell-targeted repair," thus unable to simultaneously address the wound's microenvironmental balance and the precise repair needs of damaged cells. Conventional potato-based creams have limited wound repair effects, far from meeting the clinical demand for rapid healing, especially for patients with chronic wounds, easily leading to complications such as infection and scar hyperplasia.

[0006] Safety limitations further restrict the clinical applicability of the product. To ensure shelf life, existing dressings often contain high concentrations of a single preservative, and lack low-irritation formulations designed for wounded skin. When the product is used on sensitive skin or broken wounds, it can easily cause irritation reactions such as redness, swelling, and stinging, which not only affects the patient's experience but may also worsen wound inflammation. Summary of the Invention

[0007] Based on the existing technical problems, the purpose of this invention is to provide an anti-inflammatory and moisturizing nanocomposite cream dressing containing potato extract.

[0008] Another objective of this invention is to provide a method for preparing the aforementioned nanocomposite cream dressing. This method effectively solves the problems of easy oxidation and decomposition of active ingredients in potato extract, short duration of efficacy, poor cream stability, and unsatisfactory overall anti-inflammatory, antioxidant, and moisturizing properties.

[0009] The objective of this invention is achieved through the following technical solution:

[0010] A process for preparing a potato cream dressing is characterized by: preparing potato extract through enzymatic hydrolysis and simultaneous ultrasonic-microwave extraction; preparing PLGA composite nanoparticles by combining the potato extract with PLGA; and then emulsifying and fractionally cooling the nanoparticles with poly(N-isopropylacrylamide) (PNIPAM), α-solanine, α-carboxine, potato starch, and potato protein powder to prepare a cream dressing, wherein hydroxypropyl ethyl ester is added during the fractional cooling process.

[0011] Furthermore, the preparation of potato extract involves washing potatoes with the skin on, cutting them into pieces, adding them to deionized water, adding cellulase, and enzymatically hydrolyzing them at a constant temperature of 48-52℃ for 1-2 hours to obtain an enzymatic hydrolysis system. Then, ethanol is added, and extraction is performed using ultrasound and microwave.

[0012] Furthermore, the mass ratio of the potato, deionized water and cellulase is 100:450~550:0.8~1.0.

[0013] Furthermore, the ultrasonic power is 250~280W, the microwave power is 120~150W, the temperature is 60~65℃, the extraction time is 2~3h, after extraction, the filtrate is collected by filtration and concentrated under reduced pressure to a clear extract with a relative density of 1.05~1.08 at 60℃.

[0014] Furthermore, the volume concentration of ethanol in the enzymatic hydrolysis system is 10-15%.

[0015] Furthermore, the extract was subjected to ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The ultrafiltration pressure was 0.1~0.15 MPa and the ultrafiltration flow rate was 10~20 mL / min. The ultrafiltration filtrate was collected to obtain potato extract.

[0016] The potato extract prepared using the above-mentioned enzymatic hydrolysis + ultrasound + microwave + ultrafiltration method contains a wide variety of active ingredients, including polyphenols (chlorogenic acid, caffeic acid, gallic acid), flavonoids (rutin, quercetin), and other small molecule active substances. These components can reduce inflammatory responses such as redness and itching of the skin by inhibiting the expression of key factors in inflammatory pathways (such as TNF-α, IL-6, NF-κB); at the same time, they can reduce the level of oxidative stress at the site of inflammation and alleviate skin damage caused by inflammation.

[0017] Potato extract is rich in easily oxidized active ingredients such as polyphenols and flavonoids. Direct dispersion in creams leads to decreased activity and a significant reduction in anti-inflammatory and antioxidant effects. Furthermore, in creams, free active ingredients are easily metabolized by the skin barrier and lack targeted action, making it difficult to penetrate deep into the inflamed wound layer to exert their effects. Therefore, PLGA is used as a carrier to encapsulate potato extract, improving the stability of active ingredients while exerting an EPR-like effect. This allows the active ingredients to penetrate deeper into the inflamed layer with the PLGA and prolongs their retention time, thereby improving bioavailability. However, the nanoparticles formed by PLGA-encapsulated extract are prone to aggregation during emulsification. During storage of the prepared cream, the PLGA composite nanoparticles settle, and PLGA hydrolysis in the cream causes premature leakage of active ingredients, resulting in a loss of their protective effect.

[0018] In this invention, emulsification ensures uniform dispersion of PNIPAM in the cream, and a staged cooling process promotes the formation of an ordered network structure of PNIPAM coating the PLGA surface. This allows PNIPAM molecules to gradually transition from a contracted state to a hydrophilic, expanded state as the temperature slowly decreases, synergistically forming a continuous, dense three-dimensional network structure with the oil matrix and emulsifier, anchoring the PLGA nanoparticles. The addition of hydroxypropyl ethyl ester at 45-48°C reduces the pore size of the PNIPAM network through hydrogen bonding and filling network pores, enhancing the anchoring effect of PNIPAM on the PLGA composite nanoparticles. This improves the uniformity of dispersion of the PLGA composite nanoparticles in the cream, inhibits sedimentation and aggregation, and the double coating effect prevents premature leakage of active ingredients from the PLGA composite nanoparticles into the cream.

[0019] During storage at room temperature, below the LCST, PNIPAM hydrophilically swells and expands, anchoring PLGA composite nanoparticles to maintain the cream's stability. When the cream is applied, the skin temperature is higher than the LCST, causing the PNIPAM molecular chains to transition from an expanded state to a hydrophobic contractile state. This changes the network structure, expanding the pores and releasing the anchored PLGA composite nanoparticles. These nanoparticles penetrate deep into the inflamed area through an EPR-like effect, slowly degrading and releasing potato extract for long-lasting targeted anti-inflammatory effects. After application, the contraction of PNIPAM under skin temperature reduces the cream's viscosity, resulting in a smooth, easily spreadable texture and a refreshing, non-sticky feel.

[0020] Furthermore, the PLGA composite nanoparticles are prepared by dissolving PLGA in dichloromethane, adding potato extract, ultrasonically emulsifying in an ice bath to obtain a primary emulsion, adding PVA solution and stirring to obtain a secondary emulsion, and finally rotary evaporation and freeze-drying to obtain PLGA composite nanoparticles.

[0021] Furthermore, the mass ratio of the potato extract to PLGA is 2~3:1.9~2.2.

[0022] Furthermore, in the ultrasonic emulsification process, the ultrasonic frequency is 25~35kHz and the power density is 1.5~2.5 W / cm³. 2 Ultrasonic emulsification for 5-7 minutes.

[0023] Furthermore, the mass ratio of PLGA to dichloromethane is 1:55~60, the mass ratio of PVA solution to colostrum is 1:0.5~0.8, and the mass concentration of PVA solution is 1~2%.

[0024] Furthermore, the rotary evaporation is carried out under a vacuum of -0.05 to -0.08 MPa, at a temperature of 20 to 25°C, and for 2 to 4 hours.

[0025] Furthermore, the emulsification process involves mixing hexadecyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and poly-N-isopropylacrylamide (PNIPAM) to form an oil phase, and preparing an aqueous phase by mixing purified water, glycerol, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carbohydrate, phenoxyethanol, and a mixed powder obtained by ball milling potato starch and potato protein powder. Under conditions of maintaining a temperature of 80-85°C, the oil phase is poured into the aqueous phase, and the mixture is sheared, emulsified, and homogenized to obtain an emulsion.

[0026] Furthermore, by weight, the composition includes 0.00007~0.00009 parts of α-solanine, 0.00014~0.00017 parts of α-carboxine, 0.8~1.1 parts of potato starch, 0.09~0.11 parts of potato protein powder, 4~5 parts of PLGA composite nanoparticles, 0.29~0.32 parts of triethanolamine, and 0.48~0.51 parts of polyglycerol-10 stearate. 0.19-0.21 parts of potassium cetyl phosphate, 0.8-1.0 parts of PNIPAM, 0.063-0.066 parts of phenoxyethanol, 6.5-7.5 parts of glycerin, 4.5-5.5 parts of propylene glycol, 1.45-1.55 parts of cetyl alcohol, 1.15-1.25 parts of lanolin, 2.9-3.1 parts of petrolatum, 1.9-2.1 parts of stearic acid, and 70-75 parts of purified water.

[0027] Polyglycerol-10 stearate is compounded with potassium cetyl phosphate to reduce the surface tension between the oil and water phases, forming a stable emulsion.

[0028] Furthermore, the segmented cooling process involves cooling the emulsion at 80-85°C to 58-60°C at 700-800 rpm at a rate of 3-5°C / min, maintaining this temperature for 25-30 minutes, stopping stirring, cooling to 45-48°C at a rate of 2-3°C / min, adding 0.08-0.1 parts by weight of hydroxypropyl ethyl ester, stirring at 1200-1500 rpm for 3-5 minutes, stopping stirring, cooling to 38-40°C at a rate of 1-2°C / min, adding 0.75-0.85 parts by weight of vitamin E, stirring at 700-800 rpm for 3-5 minutes, stopping stirring, and allowing it to cool naturally to room temperature.

[0029] In this invention, a segmented cooling process with a gradually decreasing cooling rate is adopted. Initially, rapid cooling reduces the overall viscosity. In the medium temperature range (60℃-45℃), medium-speed cooling guides the orderly arrangement of molecules. Low-speed cooling further solidifies the cream, causing a sharp increase in viscosity. The PNIPAM molecular chains are fully extended and form a three-dimensional network with other components to anchor the PLGA composite nanoparticles.

[0030] Most specifically, a process for preparing a potato cream dressing is characterized by comprising the following steps: S1. Preparation of potato extract S101. Take fresh potatoes, wash them with the skin on, cut them into small pieces with a diameter of 1-2 cm, add them to deionized water, then add cellulase, and enzymatically hydrolyze them at a constant temperature of 48-52℃ for 1-2 hours to obtain an enzymatic hydrolysis system. The mass ratio of potatoes, deionized water and cellulase is 100:450-550:0.8-1.0. S102. Add ethanol to the enzymatic hydrolysis system to make the ethanol volume fraction 10~15%, and extract by ultrasonic-microwave co-extraction. The ultrasonic power is 250~280W, the microwave power is 120~150W, the temperature is 60~65℃, and the extraction time is 2~3h. After the extraction is completed, filter and collect the filtrate, and concentrate it under reduced pressure to obtain a clear extract with a relative density of 1.05~1.08 at 60℃. S103. The extract was subjected to ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The ultrafiltration pressure was 0.1~0.15 MPa and the ultrafiltration flow rate was 10~20 mL / min. The ultrafiltration filtrate was collected to obtain potato extract. Preparation of S2.PLGA composite nanoparticles S201. Dissolve PLGA in dichloromethane by stirring, then add potato extract and perform ultrasonic emulsification in an ice bath environment at a frequency of 25-35 kHz and a power density of 1.5-2.5 W / cm³. 2 The colostrum is obtained by ultrasonic emulsification for 5-7 minutes, and the mass ratio of PLGA to dichloromethane is 1:55-60. S202. Add a PVA solution with a mass concentration of 1-2% to the colostrum, and stir and disperse at 4500-5500 rpm for 10-15 min to obtain a secondary emulsion, wherein the mass ratio of the PVA solution to the colostrum is 1:0.5-0.8; S203. The double emulsion was subjected to rotary evaporation at a vacuum of -0.05 to -0.08 MPa and a temperature of 20 to 25°C for 2 to 4 hours. Then, it was centrifuged at 6000 to 8000 rpm for 10 to 15 minutes. The precipitate was collected and freeze-dried to obtain PLGA composite nanoparticles. S3. Emulsification treatment S301. Place potato starch and potato protein powder in a colloid mill, grind at 3000~5000r / min for 2~3min, pause for 1~2min, repeat the grinding step 3~5 times, take out, and obtain mixed powder; S302. Take the formula amounts of cetyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and poly-N-isopropylacrylamide (PNIPAM) and mix them in a suitable container. Heat the mixture in a water bath to 80~85℃, melt it, and then place it in a homogenizer. Stir at 800~1000 r / min for 20~30 min to prepare the oil phase. S303. Take the prescribed amounts of purified water, glycerol, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carbohydrate, phenoxyethanol, and mixed powder, place them in a suitable container, heat them in a water bath to 80~85℃, dissolve them, place them in a homogenizer, and stir at 800~1000r / min for 5~10min to prepare an aqueous phase; S304. Under the condition of keeping at 80~85℃, the oil phase is slowly poured into the water phase, shear emulsified at 6000~8000r / min, and after 10~15min, it is circulated 3~5 times by a high-pressure homogenizer of 80~100MPa to obtain the emulsion. By weight, the following components are present: α-solanine 0.00007~0.00009 parts, α-carboxine 0.00014~0.00017 parts, potato starch 0.8~1.1 parts, potato protein powder 0.09~0.11 parts, PLGA composite nanoparticles 4~5 parts, triethanolamine 0.29~0.32 parts, polyglycerol-10 stearate 0.48~0.51 parts, and chlorine. Potassium pyrophosphate 0.19~0.21 parts, PNIPAM 0.8~1.0 parts, phenoxyethanol 0.063~0.066 parts, glycerin 6.5~7.5 parts, propylene glycol 4.5~5.5 parts, cetyl alcohol 1.45~1.55 parts, lanolin 1.15~1.25 parts, petrolatum 2.9~3.1 parts, stearic acid 1.9~2.1 parts, purified water 70~75 parts; S4. Segmented cooling Cool the emulsion at 80-85℃ to 58-60℃ at 700-800 rpm at a rate of 3-5℃ / min, hold for 25-30 min, stop stirring, cool to 45-48℃ at a rate of 2-3℃ / min, add 0.08-0.1 parts of hydroxypropyl ethyl ester, stir at 1200-1500 rpm for 3-5 min, stop stirring, cool to 38-40℃ at a rate of 1-2℃ / min, add 0.75-0.85 parts of vitamin E, stir at 700-800 rpm for 3-5 min, stop stirring, and allow to cool naturally to room temperature.

[0031] In this invention, α-solanine and α-carboxine, being highly active anti-inflammatory components, rapidly target and bind to receptors at sites of skin inflammation, inhibiting the release of inflammatory factors (such as TNF-α), resulting in a rapid onset of action after cream application. PNIPAM's hydrophilic-hydrophobic transition at around 32°C enables a temperature-responsive process for the active ingredients, allowing the PLGA composite nanoparticles to slowly degrade in the skin's microenvironment. This results in the continuous release of flavonoids, polyphenols, and other components from the extract, achieving long-lasting anti-inflammatory and antioxidant effects. This forms a synergistic anti-inflammatory system combining rapid onset and long-lasting action, enhancing the cream's anti-inflammatory efficacy. Furthermore, this invention utilizes a triple moisturizing system—polyol dilution, polymer film formation, and oil-based water-locking—to improve the cream's moisturizing effect.

[0032] An anti-inflammatory and moisturizing nanocomposite cream is characterized by the following steps: potato extract is prepared by enzymatic hydrolysis and ultrasonic-microwave combined extraction; PLGA composite nanoparticles are prepared by combining the potato extract with PLGA; an oil phase is prepared by mixing hexadecyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and poly-N-isopropylacrylamide (PNIPAM); an aqueous phase is prepared by mixing purified water, glycerin, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carboxine, phenoxyethanol, and a mixed powder obtained by ball milling potato starch and potato protein powder; the oil phase is poured into the aqueous phase, and emulsification and homogenization are carried out at a temperature of 80-85°C to obtain an emulsion; and then the emulsion is prepared by staged cooling.

[0033] Furthermore, by weight, the composition includes 0.00007~0.00009 parts of α-solanine, 0.00014~0.00017 parts of α-carboxine, 0.8~1.1 parts of potato starch, 0.09~0.11 parts of potato protein powder, 4~5 parts of PLGA composite nanoparticles, 0.29~0.32 parts of triethanolamine, and 0.48~0.51 parts of polyglycerol-10 stearate. 0.19-0.21 parts of potassium cetyl phosphate, 0.8-1.0 parts of PNIPAM, 0.063-0.066 parts of phenoxyethanol, 6.5-7.5 parts of glycerin, 4.5-5.5 parts of propylene glycol, 1.45-1.55 parts of cetyl alcohol, 1.15-1.25 parts of lanolin, 2.9-3.1 parts of petrolatum, 1.9-2.1 parts of stearic acid, and 70-75 parts of purified water.

[0034] Furthermore, the preparation of the potato extract involves washing the potatoes with the skin on, cutting them into pieces, adding them to deionized water, adding cellulase, and enzymatically hydrolyzing them at a constant temperature of 48-52℃ for 1-2 hours to obtain an enzymatic hydrolysis system. Then, ethanol is added, and extraction is performed using ultrasound and microwave.

[0035] Furthermore, the mass ratio of the potato, deionized water and cellulase is 100:450~550:0.8~1.0.

[0036] Furthermore, the ultrasonic power is 250~280W, the microwave power is 120~150W, the temperature is 60~65℃, the extraction time is 2~3h, after extraction, the filtrate is collected by filtration and concentrated under reduced pressure to a clear extract with a relative density of 1.05~1.08 at 60℃.

[0037] Furthermore, the extract was subjected to ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The ultrafiltration pressure was 0.1~0.15 MPa and the ultrafiltration flow rate was 10~20 mL / min. The ultrafiltration filtrate was collected to obtain potato extract.

[0038] Furthermore, the PLGA composite nanoparticles are prepared by dissolving PLGA in dichloromethane, adding potato extract, ultrasonically emulsifying in an ice bath to obtain a primary emulsion, adding PVA solution and stirring to obtain a secondary emulsion, and finally rotary evaporation and freeze-drying to obtain PLGA composite nanoparticles.

[0039] Furthermore, the mass ratio of the potato extract to PLGA is 2~3:1.9~2.2.

[0040] Furthermore, in the ultrasonic emulsification process, the ultrasonic frequency is 25~35kHz and the power density is 1.5~2.5 W / cm³. 2 Ultrasonic emulsification for 5-7 minutes.

[0041] Furthermore, the mass ratio of PLGA to dichloromethane is 1:55~60, the mass ratio of PVA solution to colostrum is 1:0.5~0.8, and the mass concentration of PVA solution is 1~2%.

[0042] Furthermore, the rotary evaporation is carried out under a vacuum of -0.05 to -0.08 MPa, at a temperature of 20 to 25°C, and for 2 to 4 hours.

[0043] Furthermore, the segmented cooling process involves cooling the emulsion at 80-85°C to 58-60°C at 700-800 rpm at a rate of 3-5°C / min, maintaining this temperature for 25-30 minutes, stopping stirring, cooling to 45-48°C at a rate of 2-3°C / min, adding 0.08-0.1 parts of hydroxypropyl ethyl ester, stirring at 1200-1500 rpm for 3-5 minutes, stopping stirring, cooling to 38-40°C at a rate of 1-2°C / min, adding 0.75-0.85 parts of vitamin E, stirring at 700-800 rpm for 3-5 minutes, stopping stirring, and allowing it to cool naturally to room temperature.

[0044] The present invention has the following technical effects: In the cream dressing prepared by this invention, the stability of the extract in the cream is improved by encapsulating it with PLGA and anchoring it with PNIPAM, which inhibits its stratification and sedimentation in the cream and ensures that the cream has a delicate texture. Combined with α-solanin and α-carboxine, it forms a synergistic targeted anti-inflammatory system with rapid onset and long-lasting effect, which effectively improves the anti-inflammatory and moisturizing effect of the cream. Attached Figure Description

[0045] Figure 1 This is a PLGA nanocomposite cream containing potato active ingredients prepared in Example 1 of the present invention. Detailed Implementation

[0046] The present invention will be specifically described below through embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.

[0047] The raw materials used in this invention are as follows: α-Solanine, α-Carboxine (purchased from Shanghai Yuanye Biotechnology Co., Ltd.), Potato Starch (purchased from Shandong Fuyang Biotechnology Co., Ltd.), Potato Protein Powder (purchased from Shandong Taijia Dongheng Biotechnology Co., Ltd.), Polylactic Acid-Glycoacetic Acid Copolymer (PLGA, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) with a particle size of 200nm, Triethanolamine (purchased from Jiangsu Tianyin Chemical Co., Ltd.), Polyglycerol-10 Stearate, Cetyl Phosphate Potassium, Cetyl Alcohol (purchased from Zhejiang Huangma Technology Co., Ltd.), Poly(N-isopropylacrylamide, PNIPAM, Thermosensitive Material) (purchased from Suzhou Nanotechnology Co., Ltd.), Hydroxypropyl Ethyl Acrylamide, Phenoxyethanol (purchased from Jiangsu Ruijia Chemical Co., Ltd.), Glycerin (purchased from Jiangsu Huashen Pharmaceutical Co., Ltd.), Propylene Glycol, Stearic Acid (purchased from BASF (China) Co., Ltd.), Vitamin E (purchased from Zhejiang Xinhecheng Co., Ltd.), Lanolin (purchased from Jiangsu Jiayuan Biotechnology Co., Ltd.), Vaseline (purchased from Jiangsu Taihe Chemical Co., Ltd.).

[0048] Example 1 A process for preparing a potato cream dressing includes the following steps: S1. Preparation of potato extract S101. Take fresh potatoes, wash them with the skin on, cut them into small pieces with a diameter of 1-2 cm, add them to deionized water, then add cellulase, and enzymatically hydrolyze them at 50℃ for 1.5 h to obtain an enzymatic hydrolysis system. During the enzymatic hydrolysis process, stir at 150 rpm for 30 s every 15 min. The mass ratio of the potato, deionized water and cellulase is 100:500:0.9. S102. Add ethanol to the enzymatic hydrolysis system. The ethanol volume fraction is 12%. Extract by ultrasonic-microwave co-extraction. The ultrasonic power is 260W, the microwave power is 140W, the temperature is 62℃, and the extraction time is 2.5h. After extraction, filter and collect the filtrate. Place it in a vacuum concentration device, set the vacuum degree to -0.04MPa, the temperature to 55℃, and concentrate it under reduced pressure to obtain a clear extract with a relative density of 1.05~1.08 at 60℃. S103. The extract was subjected to ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The ultrafiltration pressure was 0.12 MPa, the ultrafiltration temperature was maintained at 25℃, and the ultrafiltration was carried out at a constant flow rate of 15 mL / min. The ultrafiltrate was collected to obtain potato extract. Preparation of S2.PLGA composite nanoparticles S201. PLGA was added to dichloromethane and dissolved by stirring at 450 rpm. Potato extract was then added at 140 rpm, and the mixture was ultrasonically emulsified in an ice bath at a frequency of 30 kHz and a power density of 2 W / cm³. 2 The colostrum was obtained by ultrasonic emulsification for 6 minutes, and the mass ratio of PLGA to dichloromethane was 1:58. S202. At 5000 rpm, add a 1.5% PVA solution to the primary emulsion and stir and disperse at 5000 rpm for 12 min to obtain a secondary emulsion. The mass ratio of the PVA solution to the primary emulsion is 1:0.6. The PVA solution is obtained by adding PVA (degree of polymerization 1700-1800, degree of alcoholysis 88%) to deionized water, placing it in a 60℃ constant temperature water bath, and stirring continuously with a magnetic stirrer (speed 300 r / min) until completely dissolved. S203. The double emulsion was subjected to rotary evaporation at a vacuum of -0.06 MPa and a temperature of 20°C for 3 hours. Then, it was centrifuged at 7000 rpm for 12 minutes. The precipitate was collected and freeze-dried to obtain PLGA composite nanoparticles. The freeze-drying temperature was -35°C, the vacuum was -0.06 MPa, and the drying time was 18 hours. S3. Emulsification treatment S301. Place potato starch and potato protein powder in a colloid mill, grind at 4000 r / min for 3 min, pause for 1 min, repeat the grinding step 4 times, take out, and obtain mixed powder; S302. Take the formula amounts of cetyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and poly-N-isopropylacrylamide (PNIPAM) and mix them in a suitable container. Heat the mixture in a water bath to 80°C, melt it, and then place it in a homogenizer. Stir at 900 r / min for 25 min to prepare the oil phase. S303. Take the prescribed amounts of purified water, glycerol, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carbohydrate, phenoxyethanol, and mixed powder, mix them in a suitable container, heat them in a water bath to 80°C, dissolve them, and then place them in a homogenizer and stir at 900 r / min for 8 min to prepare the aqueous phase. S304. Under the condition of keeping at 80℃, the oil phase is slowly poured into the water phase, shear emulsified at 7000r / min, and after 12min, it is circulated 4 times by a 90MPa high-pressure homogenizer to obtain the emulsion. By weight, the following components are present: 0.00008 parts α-solanine, 0.00015 parts α-carboxine, 1 part potato starch, 0.1 part potato protein powder, 4.5 parts PLGA composite nanoparticles, 0.3 parts triethanolamine, 0.5 parts polyglycerol-10 stearate, 0.2 parts cetyl phosphate potassium, 0.9 parts PNIPAM, 0.065 parts phenoxyethanol, 7 parts glycerin, 5 parts propylene glycol, 1.5 parts cetyl alcohol, 1.2 parts lanolin, 3 parts petrolatum, 2 parts stearic acid, and 72 parts purified water. S4. Segmented cooling The emulsion at 80°C was cooled to 58°C at 750 rpm and 4°C / min, and kept at this temperature for 28 min. Stirring was stopped, and the emulsion was cooled to 46°C at 2°C / min. 0.09 parts of hydroxypropyl ethyl ester were added, and the emulsion was stirred at 1300 rpm for 4 min. Stirring was stopped, and the emulsion was cooled to 39°C at 1°C / min. 0.8 parts of vitamin E were added, and the emulsion was stirred at 750 rpm for 4 min. Stirring was stopped, and the emulsion was allowed to cool naturally to room temperature.

[0049] The nano-emulsion prepared in this embodiment is as follows: Figure 1 As shown, it is a creamy white color, without any grainy texture, with a uniform and delicate consistency, a slight sheen, and no layering, oil separation, or bubbles.

[0050] Apply a small amount to the back of your hand. It initially feels thick, but then spreads smoothly and evenly with gentle rubbing. After application, the skin feels refreshed and non-sticky.

[0051] Comparative Example 1 The difference from Example 1 is that PNIPAM is not added in the emulsification step, while the other steps remain the same.

[0052] During long-term storage, the cream exhibited oil-water separation, water separation, and clumping. The cream's color changed from milky white to yellowish-brown, and its gloss disappeared. It also experienced pilling upon application. This is likely because the PLGA composite nanoparticles, without the PNIPAM network structure for anchoring, are directly dispersed in the cream. Due to their high surface energy, they exhibit significant aggregation, sedimentation, and demulsification within the cream. Furthermore, the active ingredients may prematurely leak and degrade, leading to a decrease in long-lasting anti-inflammatory and other therapeutic effects.

[0053] Comparative Example 2 The difference compared to Example 1 is that, during the cooling process, hydroxypropyl ethyl ester was added when the temperature was reduced to 46°C in a single step at a rate of 4°C / min. Then, the temperature was further reduced to 39°C at a compatible rate, vitamin E was added, and then the mixture was allowed to cool naturally. The remaining steps were the same as in Example 1.

[0054] The prepared cream exhibited a noticeable grainy texture and, during long-term storage, showed signs of stratification, water separation, and agglomeration. This may be due to the rapid cooling at low temperatures, which caused the cream viscosity to increase too quickly, resulting in a sharp decrease in molecular motion. The PNIPAM molecular chains, emulsifiers, and oil crystals did not have enough time to arrange themselves in an orderly manner, forming a network structure with large pores. This resulted in poor anchoring of the PLGA composite nanoparticles, and the oil phase components (cetyl alcohol and petrolatum) formed coarse crystalline particles, leading to the noticeable grainy texture in the cream.

[0055] Stability test: Long-term storage stability test: The cream was stored under accelerated testing conditions (85% humidity, 40℃) for 3 months. Changes in the cream's properties were observed every 15 days, and the separation, sedimentation, and water separation rate (volume of separated water / total volume of cream) were recorded. The results are shown in Table 1.

[0056] Table 1:

[0057] As can be seen, the cream prepared in Example 1 has a fine texture, no gritty feel, and maintains a uniform milky white color, such as... Figure 1 As shown, as the testing period increased to 90 days, the viscosity of the cream increased from the initial 5610 mPa·s to 5930 mPa·s, an increase of 5.7%. The pH remained relatively stable throughout the process. The cream prepared in Comparative Example 1 had a fine texture initially, but as the testing period lengthened, a noticeable gritty texture appeared in the cream, and the color turned yellowish-brown. The viscosity decreased from the initial 3650 mPa·s to 2710 mPa·s, a decrease of 25.8%, and the pH also decreased significantly. The cream in Comparative Example 2 had a slightly rough and gritty texture initially, and as the testing period lengthened, the gritty texture intensified, the cream turned yellow, and the viscosity decreased from 5060 mPa·s to 4350 mPa·s, a decrease of 14.0%. The pH also decreased.

[0058] Cream samples were collected at 0, 30, 60, and 90 days of storage. The samples were centrifuged at 3000 rpm for 10 min, and the supernatant was collected. The content of polyphenolic active ingredients in the supernatant was determined by HPLC as a representative sample. The leakage rate and retention rate were calculated, and the results are shown in Table 2. The formulas for calculating the leakage rate and retention rate are as follows:

[0059]

[0060] Table 2:

[0061] It can be seen that the cream prepared in Example 1 showed little change in leakage rate as the test time increased, and the retention rate of active ingredients remained stable at over 90%. In contrast, Comparative Examples 1 and 2 showed a significant increase in leakage rate and a significant decrease in retention rate of active ingredients as the test time increased.

[0062] Animal studies on the anti-inflammatory and antioxidant effects of PLGA nanocomposite cream containing potato active ingredient: Experimental materials 1.1. Laboratory animals Sixty SPF-grade ICR mice, weighing 20-22g, were used, with half males and half females. The mice were acclimatized for one week before the experiment, with an ambient temperature of 22-25℃, humidity of 50-60%, a circadian rhythm of 12h / 12h, and free access to food and water.

[0063] 1.2. Experimental Samples Experimental samples: Cream of Example 1, Cream of Comparative Example 1 (without PNIPAM), and Cream of Comparative Example 2 (one-step cooling process) were all prepared according to the corresponding methods; Positive control drug: Compound dexamethasone cream (commercially available, purchased from Guangdong CR Shunfeng Pharmaceutical Co., Ltd.); Negative control: physiological saline.

[0064] 1.3. Reagents and Instruments Xylene (analytical grade, used to establish an inflammation model), TNF-α (tumor necrosis factor α), IL-6 (interleukin-6) ELISA kit, SOD (superoxide dismutase), MDA (malondialdehyde) kit, α-solanine / α-carbohydrate specific antibody, immunofluorescence staining kit; electronic balance, ELISA reader, cryostat, fluorescence microscope, skin permeameter, high-performance liquid chromatography (HPLC). 2. Experimental Grouping Sixty mice were randomly divided into 6 groups of 10 mice each, with 5 males and 5 females, and were treated as follows: Blank control group: No treatment was given, and the animals were fed according to routine conditions.

[0065] Model control group: After establishing the skin inflammation model, an equal volume of physiological saline was applied.

[0066] Positive control group: After establishing the skin inflammation model, compound dexamethasone cream (0.2g / animal) was applied.

[0067] Example 1 group: After establishing the skin inflammation model, the cream of Example 1 (0.2g / piece) was applied.

[0068] Comparative Example 1: After establishing the skin inflammation model, apply Comparative Example 1 cream (0.2g / piece).

[0069] Comparative Example 2: After establishing the skin inflammation model, Comparative Example 2 cream (0.2g / piece) was applied.

[0070] 3. Experimental Methods 3.1 Establishment of a mouse skin inflammation model: After the mice completed their acclimatization period, hair was removed from the back of the right ear and auricle using depilatory cream (approximately 1cm x 1cm area). The mice were allowed to recover for 24 hours to ensure the skin remained intact. 0.05mL of xylene was then applied to both the anterior and posterior surfaces of the right ear to establish an acute inflammation model.

[0071] Successful modeling criteria: Significant redness and congestion of the auricle appear 1 hour after application, and the ear thickness increases by ≥30% compared to normal.

[0072] 3.2 Administration method and cycle: Immediately after successful modeling, drug administration began. Each group received 0.2g per mouse, applied evenly to the inflamed area of ​​the right ear, once daily for 7 consecutive days. After administration, the mice were covered with plastic wrap for 1 hour to prevent licking. The plastic wrap was removed after 1 hour, and the mice were fed normally.

[0073] 3.3 Rapid Onset of Action Test: Immediate anti-inflammatory effect: The thickness of the right auricle of mice was measured using digital vernier calipers before administration (after modeling) and at 1 h, 3 h, and 6 h after administration (measured 3 times at the same location and the average value was taken). The ear swelling inhibition rate was calculated. Swelling inhibition rate = (ear thickness of model group - ear thickness of drug-treated group) / (ear thickness of model group - ear thickness of blank group) × 100%; At the same time, observe the reduction of redness and congestion of the auricle in each group and record the onset time (the earliest time when the redness and swelling are significantly reduced).

[0074] Early expression of inflammatory factors: 6 hours after drug administration, skin tissue from the right ear of mice in each group was taken, ground to prepare tissue homogenate, and the contents of TNF-α and IL-6 were detected by ELISA kit. The levels of inflammatory factors in each group were compared to verify the rapid anti-inflammatory mechanism.

[0075] 3.4 Testing of long-lasting anti-inflammatory and antioxidant capacity Long-lasting anti-inflammatory effect: On days 1, 3, 5 and 7 after administration, the middle ear thickness measurement and swelling inhibition rate calculation in section 3.3 were repeated, and the swelling inhibition rate time curve was plotted to compare the duration of anti-inflammatory effect in each group; 7 days after administration, the recovery of auricular skin in each group was observed (whether there was residual redness and swelling or pigmentation).

[0076] Antioxidant index detection: 3 days and 7 days after administration, skin tissue from the right ear of mice in each group was taken, homogenized, and SOD activity (reflecting antioxidant capacity) and MDA content (reflecting the degree of oxidative damage) were detected using a kit. The changes in the indicators of each group were compared to evaluate the long-term antioxidant effect.

[0077] Validation of the sustained-release properties of PLGA nanoparticles: Skin tissue from the right ear of mice in each group was collected 1, 3 and 7 days after drug administration. The residual amount of characteristic active ingredient (chlorogenic acid) of potato extract in the skin tissue was detected by HPLC. The release rate and residual pattern of active ingredients in Example 1 (PLGA-PNIPAM system), Comparative Example 1 (without PNIPAM) and Comparative Example 2 (process defect) were analyzed to verify the anchoring and sustained-release effect of PNIPAM on PLGA nanoparticles.

[0078] The specific steps are as follows: Sample preparation: Weigh 0.2g of skin tissue, add 1mL of 80% methanol solution, and grind into a homogenate in an ice bath; centrifuge at 4℃ and 12000rpm for 20min, collect the supernatant; filter through a 0.22μm microporous membrane to obtain the sample solution to be tested.

[0079] Reference standard preparation: Accurately weigh 10 mg of dried chlorogenic acid standard to constant weight and place it in a 20 mL volumetric flask. Add 80% methanol solution to the mark and vortex for 5 min. Sonicate for 10 min (200 W, 40 kHz) to obtain a chlorogenic acid standard stock solution with a concentration of 500 μg / mL. Accurately measure an appropriate amount of the standard stock solution and dilute it with 80% methanol solution to prepare standard working solutions with gradient concentrations of 5 μg / mL, 10 μg / mL, 20 μg / mL, 50 μg / mL, 100 μg / mL, and 200 μg / mL. Filter each concentration of standard working solution through a 0.22 μm microporous membrane, collect the filtrate, place it in a sample vial, and refrigerate at 4℃ for later use.

[0080] Detection conditions: C18 reversed-phase column (250 mm × 4.6 mm, 5 μm); mobile phase: methanol-0.1% phosphoric acid aqueous solution (volume ratio 30:70); flow rate: 1.0 mL / min; detection wavelength: 327 nm; column temperature: 30 ℃.

[0081] Data calculation: Plot a standard curve of chlorogenic acid using the reference solution and calculate the concentration of the component in skin tissue.

[0082] The formula for residual rate (%) is: (measured concentration of component in skin tissue / initial concentration of component in the administered dose) × 100%. The residual rate is calculated to analyze the sustained release pattern of active ingredients in different groups.

[0083] The test results are shown in Tables 3 and 4.

[0084] All experimental data were processed using SPSS 26.0 statistical software and expressed as mean ± standard deviation (x ± s). One-way ANOVA was used for comparisons between groups, and P < 0.05 was considered statistically significant.

[0085] The following is a summary table of the quantitative data of the experimental results. All data are expressed as mean ± standard deviation (x ± s). P < 0.05 is considered statistically significant for intergroup comparisons. The data clearly show the differences among groups in terms of rapid onset of action, long-term effect, and synergistic effect.

[0086] Table 3: Results of rapid onset of action test

[0087] Note: All indicators in Example 1 group showed statistically significant differences compared with Comparative Example 1 and Comparative Example 2 (P<0.05).

[0088] Table 4: Results of Long-Lasting Anti-inflammatory and Antioxidant Capacity Tests

[0089] Note: Higher SOD activity and lower MDA content indicate stronger antioxidant capacity; the residual chlorogenic acid rate in the skin reflects the sustained-release effect of the PLGA-PNIPAM system on potato extract; the epidermal recovery rate is calculated based on the skin thickness of the blank control group.

[0090] During the experiment, the mice in each group had normal mental state, diet, water intake and activity, and no abnormal reactions such as licking or irritation. The skin at the application site showed no allergic or irritating symptoms such as erythema, papules, lesions and ulcers, and the skin barrier integrity was good, which confirmed that the transdermal application of the cream was safe.

[0091] Based on the data in the table above, it can be seen that the cream of Example 1, with its targeted and rapid binding ability of α-solanine / α-carboxine, has a significantly faster onset of action than the comparative and positive control groups; at the same time, relying on the sustained-release effect of the PLGA-PNIPAM system, it achieves a long-lasting anti-inflammatory and antioxidant effect for 7 days, with the swelling inhibition rate maintained above 60%, the active ingredient residue rate reaching 42.3%, and better effects on clearing inflammatory cells and repairing skin.

[0092] Example 2 A process for preparing a potato cream dressing includes the following steps: S1. Preparation of potato extract S101. Take fresh potatoes, wash them with the skin on, cut them into small pieces with a diameter of 1-2 cm, add them to deionized water, then add cellulase, and enzymatically hydrolyze them at 48℃ for 2 hours to obtain an enzymatic hydrolysis system. During the enzymatic hydrolysis process, stir at 150 rpm for 30 seconds every 15 minutes. The mass ratio of the potato, deionized water and cellulase is 100:450:0.8. S102. Add ethanol to the enzymatic hydrolysis system. The ethanol volume fraction is 10%. Extract by ultrasonic-microwave co-extraction. The ultrasonic power is 250W, the microwave power is 120W, the temperature is 60℃, and the extraction time is 3h. After extraction, filter and collect the filtrate. Place it in a vacuum concentration device, set the vacuum degree to -0.03MPa, the temperature to 50℃, and concentrate it under reduced pressure to obtain a clear extract with a relative density of 1.05~1.08 at 60℃. S103. The extract was subjected to ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The ultrafiltration pressure was 0.10 MPa, the ultrafiltration temperature was maintained at 25℃, and the ultrafiltration was carried out at a constant flow rate of 10 ml / min. The ultrafiltrate was collected to obtain potato extract. Preparation of S2.PLGA composite nanoparticles S201. PLGA was added to dichloromethane and dissolved by stirring at 400 rpm. Potato extract was then added at 120 rpm, and the mixture was ultrasonically emulsified in an ice bath at a frequency of 25 kHz and a power density of 1.5 W / cm³. 2 The colostrum was obtained by ultrasonic emulsification for 7 minutes, and the mass ratio of PLGA to dichloromethane was 1:55. S202. At 4500 rpm, add a 1% PVA solution to the primary emulsion and stir and disperse at 4500 rpm for 15 min to obtain a secondary emulsion. The mass ratio of the PVA solution to the primary emulsion is 1:0.5. The PVA solution is obtained by adding PVA (degree of polymerization 1700-1800, degree of alcoholysis 88%) to deionized water, placing it in a 60℃ constant temperature water bath, and stirring continuously with a magnetic stirrer (speed 300 r / min) until completely dissolved. S203. The double emulsion was subjected to rotary evaporation at a vacuum of -0.05 MPa and a temperature of 25°C for 2 hours. Then, it was centrifuged at 6000 rpm for 15 minutes. The precipitate was collected and freeze-dried to obtain PLGA composite nanoparticles. The freeze-drying temperature was -40°C, the vacuum was -0.05 MPa, and the drying time was 20 hours. S3. Emulsification treatment S301. Place potato starch and potato protein powder in a colloid mill, grind at 3000 r / min for 3 min, pause for 2 min, repeat the grinding step 3 times, take out, and obtain mixed powder; S302. Take the formula amounts of cetyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and poly-N-isopropylacrylamide (PNIPAM) and mix them in a suitable container. Heat the mixture in a water bath to 85°C, melt it, and then place it in a homogenizer. Stir at 800 r / min for 30 min to obtain the oil phase. S303. Take the prescribed amounts of purified water, glycerol, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carbohydrate, phenoxyethanol, and mixed powder, mix them in a suitable container, heat them in a water bath to 85°C, dissolve them, and then place them in a homogenizer and stir at 800 r / min for 10 min to obtain an aqueous phase. S304. Under the condition of keeping at 85℃, the oil phase is slowly poured into the aqueous phase, shear emulsified at 6000r / min, and after 15min, it is circulated 5 times by an 80MPa high-pressure homogenizer to obtain the emulsion. By weight, the following components are present: 0.00007 parts α-solanine, 0.00014 parts α-carboxine, 0.8 parts potato starch, 0.09 parts potato protein powder, 4 parts PLGA composite nanoparticles, 0.29 parts triethanolamine, 0.48 parts polyglycerol-10 stearate, 0.19 parts cetyl phosphate potassium, 0.8 parts PNIPAM, 0.063 parts phenoxyethanol, 6.5 parts glycerin, 4.5 parts propylene glycol, 1.45 parts cetyl alcohol, 1.15 parts lanolin, 2.9 parts petrolatum, 1.9 parts stearic acid, and 70 parts purified water. S4. Segmented cooling The emulsion at 85°C was cooled to 58°C at 700 rpm and 3°C / min, and kept at this temperature for 30 min. Stirring was stopped, and the emulsion was cooled to 45°C at 2°C / min. 0.1 part of hydroxypropyl ethyl ester was added, and the emulsion was stirred at 1200 rpm for 5 min. Stirring was stopped, and the emulsion was cooled to 38°C at 1°C / min. 0.85 part of vitamin E was added, and the emulsion was stirred at 700 rpm for 5 min. Stirring was stopped, and the emulsion was allowed to cool naturally to room temperature.

[0093] Example 3 A process for preparing a potato cream dressing includes the following steps: S1. Preparation of potato extract S101. Take fresh potatoes, wash them with the skin on, cut them into small pieces with a diameter of 1-2 cm, add them to deionized water, then add cellulase, and enzymatically hydrolyze them at 52℃ for 1 hour to obtain an enzymatic hydrolysis system. During the enzymatic hydrolysis process, stir at 150 rpm for 30 seconds every 15 minutes. The mass ratio of the potatoes, deionized water and cellulase is 100:550:1.0. S102. Add ethanol to the enzymatic hydrolysis system. The ethanol volume fraction is 15%. Extract by ultrasonic-microwave co-extraction. The ultrasonic power is 280W, the microwave power is 150W, the temperature is 65℃, and the extraction time is 2h. After extraction, filter and collect the filtrate. Place it in a vacuum concentration device, set the vacuum degree to -0.05MPa, and the temperature to 60℃. Concentrate under reduced pressure to obtain a clear extract with a relative density of 1.05~1.08 at 60℃. S103. The extract was subjected to ultrafiltration using an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The ultrafiltration pressure was 0.15 MPa, the ultrafiltration temperature was maintained at 25℃, and the ultrafiltration was carried out at a constant flow rate of 20 ml / min. The ultrafiltrate was collected to obtain potato extract. Preparation of S2.PLGA composite nanoparticles S201. PLGA was added to dichloromethane and dissolved by stirring at 500 rpm. Potato extract was then added at 150 rpm, and the mixture was ultrasonically emulsified in an ice bath at a frequency of 35 kHz and a power density of 2.5 W / cm³. 2 The PLGA was ultrasonically emulsified for 5 minutes to obtain the primary emulsion, and the mass ratio of PLGA to dichloromethane was 1:60. S202. At 5500 rpm, add a 2% PVA solution to the primary emulsion and stir and disperse at 5500 rpm for 15 min to obtain a secondary emulsion. The mass ratio of the PVA solution to the primary emulsion is 1:0.8. The PVA solution is obtained by adding PVA (degree of polymerization 1700-1800, degree of alcoholysis 88%) to deionized water, placing it in a 65℃ constant temperature water bath, and continuously stirring with a magnetic stirrer (speed 300 r / min) until completely dissolved. S203. The double emulsion was subjected to rotary evaporation at a vacuum of -0.08 MPa and a temperature of 25°C for 4 hours. Then, it was centrifuged at 8000 rpm for 10 minutes. The precipitate was collected and freeze-dried to obtain PLGA composite nanoparticles. The freeze-drying temperature was -35°C, the vacuum was -0.08 MPa, and the drying time was 15 hours. S3. Emulsification treatment S301. Place potato starch and potato protein powder in a colloid mill, grind at 5000 r / min for 3 min, pause for 1 min, repeat the grinding step 5 times, take out, and obtain mixed powder; S302. Take the formula amounts of cetyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and poly-N-isopropylacrylamide (PNIPAM) and mix them in a suitable container. Heat the mixture in a water bath to 85°C, melt it, and then place it in a homogenizer. Stir at 1000 r / min for 20 min to obtain the oil phase. S303. Take the prescribed amounts of purified water, glycerol, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carbohydrate, phenoxyethanol, and mixed powder, mix them in a suitable container, heat them in a water bath to 85°C, dissolve them, and then place them in a homogenizer and stir at 1000 r / min for 5 min to obtain an aqueous phase. S304. Under the condition of keeping at 85℃, the oil phase is slowly poured into the water phase, shear emulsified at 8000r / min, and after 10min, it is circulated 3 times by a 100MPa high-pressure homogenizer to obtain the emulsion. By weight, the following components are present: α-solanine 0.00009 parts, α-carboxine 0.00017 parts, potato starch 1.1 parts, potato protein powder 0.11 parts, PLGA composite nanoparticles 5 parts, triethanolamine 0.32 parts, polyglycerol-10 stearate 0.51 parts, cetyl phosphate potassium 0.21 parts, PNIPAM 1.0 part, phenoxyethanol 0.066 parts, glycerin 7.5 parts, propylene glycol 5.5 parts, cetyl alcohol 1.55 parts, lanolin 1.25 parts, petrolatum 3.1 parts, stearic acid 2.1 parts, and purified water 75 parts. S4. Segmented cooling The emulsion at 85°C was cooled to 60°C at 800 rpm at a rate of 5°C / min, held at this temperature for 25 min, and then the stirring was stopped. The emulsion was then cooled to 48°C at a rate of 3°C / min, and 0.08 parts of hydroxypropyl ethyl ester were added. The emulsion was stirred at 1500 rpm for 3 min, and then the stirring was stopped. The emulsion was then cooled to 40°C at a rate of 2°C / min, and 0.75 parts of vitamin E were added. The emulsion was stirred at 800 rpm for 3 min, and then the stirring was stopped. The emulsion was allowed to cool naturally to room temperature.

Claims

1. A preparation process for a potato cream dressing, characterized in that: Potato extract was prepared through enzymatic hydrolysis and ultrasonic-microwave combined extraction. The potato extract was then combined with PLGA to prepare PLGA composite nanoparticles. These nanoparticles were then sequentially emulsified with poly(N-isopropylacrylamide) PNIPAM, α-solanine, α-carboxine, potato starch, and potato protein powder, followed by staged cooling to prepare a cream dressing. Hydroxypropyl ethyl ester was added during the staged cooling process. The staged cooling involved cooling the emulsion from 80-85°C to 58-60°C at 700-800 rpm at a rate of 3-5°C / min, holding the temperature for 25-30 min, stopping stirring, cooling to 45-48°C at a rate of 2-3°C / min, adding 0.08-0.1 parts by weight of hydroxypropyl ethyl ester, stirring at 1200-1500 rpm for 3-5 min, stopping stirring, cooling to 38-40°C at a rate of 1-2°C / min, and adding 0. 75-0.85 parts by weight of vitamin E are stirred at 700-800 r / min for 3-5 min, then stirring is stopped and the mixture is allowed to cool naturally to room temperature. The emulsification process involves mixing cetyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and PNIPAM to form an oil phase. Purified water, glycerol, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carboxine, phenoxyethanol, and a mixed powder obtained by ball milling potato starch and potato protein powder are used to form an aqueous phase. The oil phase is poured into the aqueous phase under a temperature of 80-85℃, and the mixture is sheared, emulsified, and homogenized to obtain an emulsion.

2. The preparation process of a potato cream dressing as described in claim 1, characterized in that: To prepare the potato extract, the potatoes were washed with the skin on, cut into pieces, added to deionized water, and then cellulase was added. The mixture was kept at a constant temperature of 48-52℃ for 1-2 hours to obtain an enzymatic hydrolysis system. Then, ethanol was added, and extraction was performed using ultrasound and microwave.

3. The preparation process of a potato cream dressing as described in claim 1 or 2, characterized in that: The ultrasonic-microwave combined extraction uses an ultrasonic power of 250-280W, a microwave power of 120-150W, a temperature of 60-65℃, and an extraction time of 2-3 hours. After extraction, the filtrate is collected by filtration and concentrated under reduced pressure to a clear extract with a relative density of 1.05-1.08 at 60℃.

4. The preparation process of a potato cream dressing as described in claim 3, characterized in that: The PLGA composite nanoparticles are prepared by dissolving PLGA in dichloromethane, adding potato extract, ultrasonically emulsifying in an ice bath to obtain a primary emulsion, adding PVA solution and stirring to obtain a secondary emulsion, and finally rotary evaporation and freeze-drying to obtain PLGA composite nanoparticles.

5. The preparation process of a potato cream dressing as described in claim 4, characterized in that: The mass ratio of potato extract to PLGA is 2~3:1.9~2.

2.

6. The preparation process of a potato cream dressing as described in claim 5, characterized in that: The mass ratio of PLGA to dichloromethane is 1:55~60, the mass ratio of PVA solution to colostrum is 1:0.5~0.8, and the mass concentration of PVA solution is 1~2%.

7. The preparation process of a potato cream dressing as described in claim 6, characterized in that: By weight, the following components are present: α-solanine 0.00007~0.00009 parts, α-carboxine 0.00014~0.00017 parts, potato starch 0.8~1.1 parts, potato protein powder 0.09~0.11 parts, PLGA composite nanoparticles 4~5 parts, triethanolamine 0.29~0.32 parts, polyglycerol-10 stearate 0.48~0.51 parts, and chlorine. Potassium pyrophosphate 0.19~0.21 parts, PNIPAM 0.8~1.0 parts, phenoxyethanol 0.063~0.066 parts, glycerin 6.5~7.5 parts, propylene glycol 4.5~5.5 parts, cetyl alcohol 1.45~1.55 parts, lanolin 1.15~1.25 parts, petrolatum 2.9~3.1 parts, stearic acid 1.9~2.1 parts, purified water 70~75 parts.

8. An anti-inflammatory and moisturizing nanocomposite cream, characterized in that: Potato extract was prepared through enzymatic hydrolysis and ultrasonic-microwave combined extraction. The potato extract was then combined with PLGA to prepare PLGA composite nanoparticles. An oil phase was prepared by mixing hexadecyl alcohol, lanolin, petrolatum, stearic acid, triethanolamine, polyglycerol-10 stearate, potassium cetyl phosphate, and poly(N-isopropylacrylamide) (PNIPAM). An aqueous phase was prepared by mixing purified water, glycerol, propylene glycol, PLGA composite nanoparticles, α-solanine, α-carboxine, phenoxyethanol, and a mixture of potato starch and potato protein powder obtained by ball milling. The oil phase was then added to the aqueous phase. Emulsification and homogenization are carried out at 80-85℃ to obtain an emulsion, which is then subjected to staged cooling to prepare a cream. The staged cooling is as follows: the emulsion at 80-85℃ is cooled to 58-60℃ at 700-800 rpm at a rate of 3-5℃ / min, held at this temperature for 25-30 min, stirring is stopped, and the temperature is cooled to 45-48℃ at a rate of 2-3℃ / min. 0.08-0.1 parts by weight of hydroxypropyl ethyl ester are added, and the mixture is stirred at 1200-1500 rpm for 3-5 min. Stirring is stopped, and the temperature is cooled to 38-40℃ at a rate of 1-2℃ / min. 0.75-0.85 parts by weight of vitamin E are added, and the mixture is stirred at 700-800 rpm for 3-5 min. Stirring is stopped, and the mixture is allowed to cool naturally to room temperature.

Citation Information

Patent Citations

  • Preparation method of fusidic acid cream

    CN120204124A

  • Extraction method of potato peel polyphenol and application of potato peel polyphenol in antioxidation

    CN120617369A